83 The Feasibility of an Interdisciplinary Led Community Based Functional Training Group for Frail Older Adults in a Post-Acute Orthogeriatric Unit. (16th September 2019) - McDaid, Edel; Johnston, Aoife; Ross, Elaine; Cogan, Lisa
Abstract: Background: Reduced ability to perform instrumental activities of daily living (IADLs) can lead to a difficult transition from hospital to home, increased dependence and diminished quality of life (1). A novel IADL group for frail older adults 'Ready Steady Home' was completed to facilitate transition from hospital to home. Methods: A single centre prospective study was undertaken in a Post-Acute Orthogeriatric Rehabilitation Care unit. A sample of convenience was recruited over a 3 month period. All subjects invited to participate had been referred for Physiotherapy and Occupational Therapy, medically stable, able to give consent, mobile with/without an aid and had a goal of community ambulation and IADLS. The one hour intervention consisted of a car transfer, outdoor mobility on a busy footpath, road crossing, negotiating a busy shop, completing shopping task and financial management. A self-reported modified Client Satisfaction Questionnaire (CSQ-8) was completed by all subjects post intervention. Data was analysed using descriptive statistics. Results: Twelve participants (female (12); mean age 83.7 years, mean LOS 32.75 days) completed the intervention and were included in the data. All were frail with a Clinical Frailty Scale score ≥ 5, mild (n=4), moderate (n=7) and severe frailty (n=1). Primary diagnosis was femoral fracture (n=7), hip surgery revision (n=2), deconditioning (n=2) and pelvic fracture (n=1). All used a unilateral (n=5) and/or bilateral mobility aid (n=7). The mean CSQ-8 score was 27/32 indicating high satisfaction with the intervention. No adverse events occurred. Common themes reported were improved confidence with community ambulation, preparation for home and re-integration into the community. Conclusion: This study indicates that an interdisciplinary intervention addressing community based IADLS was feasible, safe and effective in a frail Orthogeriatric inpatient cohort. Further research is required to evaluate the effectiveness of this therapy intervention in improving hospital to home transition and potential reduction in LOS.